A 9-year retrospective study of poisoning-related deaths in Southwest China (Sichuan). (January 2021) - Xiao, Li; Ye, Yi; Wang, Yanjun; Dai, Xinhua; Fang, Shiyong; Wei, Ying; Zheng, Yuzi; Wu, Hao; Fu, Yinqiang; Liao, Linchuan
Highlights: It is the first report on poisoning-related cases in Southwest China. The poisoning data are classified by multiple methods. A total of dozens of toxicants are found in all poisoning cases. Abstract: Poisoning is an increasing and significant burden that causes morbidity and mortality worldwide. In this retrospective study, poisoning-related cases that occurred in 19 cities and prefectures in Sichuan, Southwest China, between 2010 and 2018 were collected from the West China Forensic Medical Center of Sichuan and Public Security Bureaus. A total of 782 poisoning-related deaths were recorded, and their demographic characteristics, season of death, type of poison, and manner and cause of death were analysed. Of these cases, the victims were predominantly male (65.3%), and the 21∼50-year-old age group included the most victims (63.2%). The rural incidence was 71%. The most common poisoning agent was pesticide (40%), followed by toxic gases (32%), and there were cases of poisoning by poisonous animals and plants that are not common in other regions of China. The predominant manner of poisoning death was accident (50%), followed by suicide (38.3%) and homicide (5.0%). In this study, relevant information on poisoning-related cases was collected and compared with the poisoning data from other areas of China and foreign countries to provide guidance for the formulation of public health policies in Sichuan, Southwest China.